The Effect of Effleurage Massage on Reducing the Degree of Dysmenorrhea in Adolescent Girls in Sukarama Village, Cianjur Regency, Indonesia - Roslinawati Roslinawati (HM Publisher, 2023)
Effleurage massage can provide a sense of relaxation and calm that can help reduce stress. By increasing blood flow to the pelvic area, effleurage techniques can help improve the supply of nutrients and oxygen to the tissues, potentially speeding recovery and reducing pain. This study aimed to determine the effect of effleurage massage on reducing the degree of dysmenorrhea in adolescent girls in Sukarama Village, Cianjur Regency, Indonesia. This study is a quasi-experimental research with a pre-post-test approach and uses primary data obtained from direct observation of respondents. A total of 30 research subjects took part in this study. This study shows that the intervention of providing effleurage massage is effective in reducing pain intensity in dysmenorrhea sufferers. There was a decrease in pain intensity after giving effleurage massage and it was stated to be statistically different, p<0.05. In conclusion, there is an effect of effleurage massage on reducing the degree of dysmenorrhea in adolescent girls in Sukarama Village, Cianjur Regency, Indonesia.